Drivers of Marine Phytoplankton Diversity and Connectivity in the Galápagos Archipelago Spanning an ENSO Cycle - Prisca Lim; Harvey Seim; Oliva Torano; Erika Neave; Se Hyeon Jang; Zackary Johnson; Sara Haines; Scott Gifford; Natalie Cohen; Carly M. Moreno; Margarita Lankford; Cristina Vintimilla Palacios; et al. (Environmental Microbiology, 2025)
The Galápagos Islands are a biodiversity hotspot, largely due to the Equatorial Undercurrent (EUC) which supplies nutrient‐rich waters to the euphotic zone and supports enhanced levels of primary productivity performed by phytoplankton. Understanding phytoplankton responses to changing environmental conditions is crucial for regional conservation and management efforts. Research cruises conducted between 2014 and 2022, spanning a major El Niño event in 2015 and a La Niña event in 2022, observed varying oceanic conditions and diverse phytoplankton community composition. At most EUC‐influenced stations, larger‐sized phytoplankton groups (≥ 5 μm) were dominant while warmer, oligotrophic sites favoured smaller‐sized phytoplankton groups (